Analysis of Carbon Monoxide Exposure and Its Effect to Lung Function of Parking Officer in Basement Mal X Pekanbaru - Indi Esha; Dedi Afandi; Viktor Amrifo (Program Pascasarjana Universitas Riau, 2017)
A Study on the effect of carbon monoxide exposure on lung function of parking officers in basement Mall X Pekanbaru were carried out in January 2017. The research aim at describing carbon monoxide air ambient in basement Mall X Pekanbaru as well as respiratory state of parking officers and analysing carbon monoxide exposure and lung function relationship. The result showed that carbon monoxide concentration ranged from 2,8 – 11,5 ppm with average of 6,23 ppm. Apparently carbon monoxide exposure had significant correlation (r = -0,795) with lung function of parking officers in basement of the Mall X Pekanbaru. Respiration state of the parking officers account for 16,7% impaired lung function examined by spirometri. Working period more than 1 year related to that of impaired lung function. Other factors such as used of self protection device, smoking habit, medical record showed a significant correlation with lung function.